Vestibular incision subperiosteal tunnel access with titanium-prepared platelet-rich fibrin - A golden approach for treating multiple recession defects in esthetic zone - Manvi Chandra Agarwal; Priyansha Rathore; Shiva Shankar Gummaluri; Prerna Agarwal; Sanju Kumari (Wolters Kluwer Medknow Publications, 2019)
Gingival recession is defined as apical migration of marginal gingival tissue causing the exposure of root surface. Abnormal brushing techniques, trauma, anatomical presence of tooth, caries, and improper oral hygiene measures are some of the problems leading to gingival recession. Several treatment modalities such as coronary advanced flaps and free gingival grafts have been used for the treatment of gingival recession defects and showed good results. However, while treating multiple gingival recessions, some new treatment modalities were introduced in literature. Vestibular incision subperiosteal tunnel access (VISTA) as a minimally invasive technique for root coverage was introduced with various advantages such as no secondary surgical site needed for harvestment of donor tissue and it provides excellent esthetic results with decreased patient morbidity. The present case report emphasizes on the treatment of multiple gingival recessions in the maxillary anterior teeth region using VISTA with titanium-prepared platelet-rich fibrin.